2018
DOI: 10.1016/j.heliyon.2018.e00897
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 efficiently removes indigo carmine dyes from polluted water

Abstract: MnO2 is identified as a highly efficient sonocatalyst and sonophotocatalyst for the complete removal of even very small concentration of Indigo carmine (IC) dye pollutant from water. The effect of various reaction parameters, viz. dosage of the catalyst, concentration of pollutant, volume of reaction system, pH, dissolved gases, presence of anions/salts and oxidants etc. on the rate of degradation is evaluated and optimum parameters are identified. The degradation follows variable kinetics depending on the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 68 publications
(131 reference statements)
1
12
0
Order By: Relevance
“…It is also noted that the rate of degradation of remazol black at 5 mg/L is greater than that of 25 mg/L. This result is in agreement with the previous one where we showed that when the dye concentration increased, then the pollutant load influenced the free radicals produced and therefore decreased the degradation of the dye [12,32].…”
Section: Kinetic Study Of Degradationsupporting
confidence: 93%
See 1 more Smart Citation
“…It is also noted that the rate of degradation of remazol black at 5 mg/L is greater than that of 25 mg/L. This result is in agreement with the previous one where we showed that when the dye concentration increased, then the pollutant load influenced the free radicals produced and therefore decreased the degradation of the dye [12,32].…”
Section: Kinetic Study Of Degradationsupporting
confidence: 93%
“…An increased number of dye molecules and insufficient concentration of the active radicals decreased the efficiency of the decomposition process [29][30][31]. Similar results were obtained for the degradation of indigo carmine with manganese dioxide [32]. Indeed, an increase in the initial concentration of dye would increase the pollutant load, leads the decrease in catalytic activity and also prolongs the degradation time [33].…”
Section: Influence Of Some Parameters On the Degradation Of Remazol Blackmentioning
confidence: 71%
“…BNNS nanoparticles are in fact an excellent adsorbent for various organic pollutants predominantly due to its B-N bonds polarity which would favour the transfer of electrons with the aromatic organic molecules leading to physisorption reaction [5]. With the present of sodium salt (common cation in all cases was Na + ), anions could increase the adsorption capability of the humic acid onto the membrane [28]. It seems that one of its advantages had turned out to be a drawback if it were to be incorporated in the membrane matrix without prior modification.…”
Section: Resultsmentioning
confidence: 99%
“…[ 9 , 10 , 11 , 12 , 13 ]. In addition, MnO 2 can also be available for environmental technology such as dye degradation [ 14 , 15 ], wastewater treatment [ 16 , 17 ], photocatalytic degradation of organic pollutants [ 18 , 19 , 20 , 21 , 22 , 23 ], and photo-electrochemical hydrogen production [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%